Audiovisuelle Rhythmen. Filmmusik, Bewegungskomposition und die dynamische Affizierung des Zuschauers - Bakels, Jan-Hendrik (Cinepoetics. Poetologien audiovisueller Bilder, 2016)
The book explores the relationship of movement and music in film to study the aesthetic principles of audience affect. It begins by a reconstructive analysis and theoretical reflection on the rhythmicity of films - and goes on to show the extent to which the rhythmic dimension of audiovisual images offers access to intersubjective strategies to induce affect in the movie theater.